CSRC's random inspection and capital market information efficiency: An empirical evidence from stock price synchronicity - Xue Xia; Fei Teng; Liping Xu; Yu Xin (China Journal of Accounting Studies (CJAS), 2024)
The random inspection of the China Securities Regulatory Commission (CSRC) is an important policy for practicing "standardizing regulatory behavior and innovating management modes". This study investigates how CSRC's random affect capital market information efficiency from the perspective of stock price synchronicity. Using a sample of China's non-financial A-share firms from 2013 to 2019, we find that random inspections significantly reduced the stock price synchronicity of inspected firms. Random inspections could increase the probability of releasing management earnings forecasts, media coverage and investor attention, and thereby improve information efficiency. Further study finds that the effect of random inspections on stock price synchronicity is stronger for non-state controlled firms, districts with more listed firms, and districts with more transparent government. This study enriches the literature on the consequences of random inspections and extends our knowledge of the relationship between regulatory innovations and the information efficiency of the capital market.
Keywords: 650; capital market information efficiency; CSRC's random inspection; regulatory innovations; stock price synchronicity